2009
DOI: 10.1111/j.1472-8206.2009.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological screening of bryophyte extracts that inhibit growth and induce abnormal phenotypes in human HeLa cancer cells

Abstract: Antitumor activities of substances from natural sources apart from vascular plants and micro-organisms have been poorly investigated. Here we report on a pharmacological screening of a bryophyte extract library using a phenotypic cell-based assay revealing microtubules, centrosomes and DNA. Among the 219 moss extracts tested, we identified 41 extracts acting on cell division with various combinations of significant effects on interphasic and mitotic cells. Seven extracts were further studied using a cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The interest in bryophyte chemical composition has been growing ever since the presence of a high number of biologically active compounds in their composition was demonstrated (Basile et al, 1999;Fu et al, 2012;Asakawa et al, 2013). Many compounds isolated from bryophytes have shown high biological activity (Krzaczkowski et al, 2009;Üçüncü et al, 2010). Likewise, extracts of bryophytes have shown multiple kinds of biological activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in bryophyte chemical composition has been growing ever since the presence of a high number of biologically active compounds in their composition was demonstrated (Basile et al, 1999;Fu et al, 2012;Asakawa et al, 2013). Many compounds isolated from bryophytes have shown high biological activity (Krzaczkowski et al, 2009;Üçüncü et al, 2010). Likewise, extracts of bryophytes have shown multiple kinds of biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of bryophytes have demonstrated well-expressed antibacterial, antifungal and antiviral activities. Moreover, in several studies, their cytoxicity in respect to cancer cells has been demonstrated, as well as antioxidant, antiplatelet, antithrombin, insecticidal and neuroprotective activities, ability to inhibit a number of biochemically important enzymes, and other kinds of activities (Spjut et al, 1986;Wang et al, 2005;Sing et al, 2006;Krzaczkowski et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In most of the cases, the observed phenotypic changes were mainly a prometaphase-metaphase block and/or an impaired cytoskeleton organization. Such changes are frequently encountered after treating HeLa cells with classic antimitotic drugs [8] (see Supporting Information section for major phenotypic changes induced by 13 reference compounds including anticancer drugs or mitotic blockers). Six extracts (2 from Equisetaceae and 4 from Thelypteridaceae) showed unique effects characterized by the impairment of γ-tubulin labelling on the centrosomes of both interphasic and mitotic cells, together with the presence of monopolar mitotic spindles.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro cytotoxic activity of M. convoluta ethyl acetate extract on human liver and lung cancer cell lines (H1299 and HepG2) were reported, where petroleum ether and n-butanol extracts showed no activity [187] . Bryophytes extracts which inhibit growth and induce abnormal phenotypes in human HeLa cancer cells with significant effects on interphasic and mitotic cells, have been screened pharmacologically [188] . Luteolin, another biologically active compound, reported from various bryophytes and higher groups of plants is reported to induce apoptosis, prevent carcinogenesis and reduce tumor growth in vivo.…”
Section: Othersmentioning
confidence: 99%